DUKUNGAN KELUARGA DAN MODAL PSIKOLOGIS MAHASISWA - Prihatsanti, Unika (Jurnal Psikologi, 2014)
Psychological capital in students is a positive psychological condition that enables students to deal with uncomfortable situation so that they could finish their study in college and prepare themselves to enter professional world. This study aims to test the correlation between family support and psychological capital in college students. In total, 126 students joined the study. Data were collected using the Family Support Scale (21 items; Î± = 0.892) and the Psychological Capital Scale (20 items; Î± = 0.892). Data analysis using simple regression analysis revealed a positive significant correlation between family support and psychological capital (r = 0.215; p = 0.008).